IMPORTANCE OF DIDACTIC CONDITIONS IN ACTIVATING STUDENTS’ INDEPENDENT EDUCATION - Khaitova Shakhnoza Daniyarovna; Nurmukhamdieva Lola Alisherovna (Journals Park Publishing, 2023)
Independent education as a method of educational activity is a means of forming the necessary type of personality in the present time. The goal of teaching in the process of independent education is the formation of a system of self-developing connections that adequately reflects the objective reality, and it becomes the personal goal of each student.
Keywords: Independent education, activation, pedagogical proc